‘The East Is Both Gentle and Brilliant…’: Pantuns and Peacocks of Nikolay Gumilyov - Elena Yur'evna Kulikova (Известия Уральского федерального университета. Серия 2: Гуманитарные науки, 2015)
The article considers the pantun of Nikolay Gumilyov Goncharova and Larionov, reflecting Eastern motives. The avant-garde discoveries of artists are written into the rigid form of a Malay genre. The article uses the method of immanent and intertextual analysis of the text, entering intermedial space through comparison with visual arts. The result of the research is the study of a forme fixe of Silver Age poetry: the genre of the pantun based on national Eastern poetry and mediaeval lyrical poetry with oriental motives which becomes part of the new way of expression. Gumilyov presents an Eastern theme in an Eastern form.